Representations of Black Women in the Chicago Defender as Race Pride and Race Shame Examples, 1919-1923 - Zimmermann, Zachary (My University, 2010)
Despite the distinctive importance of black women and the Chicago Defender during and following the Great Migration and Progressive Era years, there continues to be a lack of analysis concerning their representations in Chicago's famous newspaper. Because the respectability of black women was the standard by which the black middle class and elite marked racial advancement, their images in the Defender were conscious and significant constructions. Thus, this study analyzes the representations of black women within the Defender's race advocacy function, finding that examples of race pride and race shame operated in conjunction and were influenced by early twentieth century, black uplift ideology. Correspondingly, the relationship between uplift ideology and the Defender is also analyzed as the duality of sexual, racial, and class hierarchies of the former were influential on the newspaper's race advocacy function. Examples of black women were used with two intents: first, to display distinctions and class hierarchy within the black population, and second, to influence the values and behaviors of the black population. Included is a descriptive analysis of the role model, race pride representation of black women, the corresponding negative, race shame archetype, as well as a quantitative analysis of the polarized examples of black women on the paper's front page. The years examined are 1919-1923 due to the transitional state of: American race relations, the black community, sexual mores, black nationalism, and the Defender.
Keywords: Chicago Defender; Stereotypes (Social psychology) in mass media; African American women in mass media; Chicago (Ill.)--Race relations--History; Racism--Illinois--Chicago--History